INTEGRATED MANAGEMENT OF CHROMOLAENA ODORATA EMPHASIZING THE CLASSICAL BIOLOGICAL CONTROL - SOEKISMAN TJITROSEMITO (SEAMEO BIOTROP, 1998)
Chromolaena odorata, Siam weed, a very important weed of Java Island (Indonesia) is native to Central and South America. In the laboratory it showed rapid growth (1.15 g/g/week) in the first 8 weeks of its growth. The biomass was mainly as leaves (LAR : 317.50 cm'/g total weight). It slowed down in the following month as the biomass was utilized for stem and branch formation. This behavior supported the growth of C. odorata into a very dense stand. It flowered, fruited during the dry season, and senesced following maturation of seeds from inflorescence branches. These branches dried out, but soon the stem resumed aggressive growth following the wet season. Leaf biomass was affected by the size of the stem in its early phase of regrowth, but later on it was more affected by the number of branches. The introduction of Pareuchaetes pseudoinsulata to Indonesia, was successful only in North Sumatera. In Java it has not been reported to establish succesfully. The introduction of another biological control agent, Procecidochares conneca to Indonesia was shown to be specific and upon release in West Java it established immediately. It spread exponentially in the first 6 months of its release. Field monitoring continues to evaluate the impact of the agents. Other biocontrol agents (Actmole anteas and Conotrachelus) wilt be introduced to Indonesia in 1997 through ACIAR Project on the Biological Control of Chromolaena odorata in Indonesia and Papua New Guinea. Keywords: Indonesia / North Sumatra / West Java / Biological control / Chromolaena odorata i Pareuchaetes pseudoinsulata I Procecidochares conneca.